Assessment of Patients' Knowledge and Awareness about their Rights and Duties - Jasim N. Al-Asadi; Alaa H. Abed; Sabah A. Shami; Husam Al-Shammary; Shukrya K. Khalaf (Kufa Journal for Nursing Sciences)
Background: patient's right is the one of the basic issues in health care. Implementation of patient's rights law is intended to secure good medical practice and can improve the doctor-patient relationship if both of them are aware of it.